Fluorobenzene and Water‐Promoted Rapid Growth of Vertical Graphene Arrays by Electric‐Field‐Assisted PECVD. Issue 10 (17th January 2023) - Shen, Chao; Xu, Shichen; Chen, Zhuo; Ji, Nannan; Yang, Jinhui; Zhang, Jin
Abstract: Vertical graphene (VG) arrays show exposed sharp edges, ultra‐low electrical resistance, large surface‐to‐volume ratio, and low light reflectivity, thus having great potential in emerging applications, including field emission, sensing, energy storage devices, and stray light shields. Although plasma enhanced chemical vapor deposition (PECVD) is regarded as an effective approach for the synthesis of VG, it is still challenging to increase the growth rate and height of VG arrays simultaneously. Herein, a fluorobenzene and water‐assisted method to rapidly grow VG arrays in an electric field‐assisted PECVD system is developed. Fluorobenzene‐based carbon sources are used to produce highly electronegative fluorine radicals to accelerate the decomposition of methanol and promote the growth of VG. Water is applied to produce hydroxyl radicals in order to etch amorphous carbon and accelerate the VG growth. The fastest growth rate can be up to 15.9 µm h −1 . Finally, VG arrays with a height of 144 µm are successfully synthesized at an average rate of 14.4 µm h −1 . As a kind of super black material, these VG arrays exhibit an ultra‐low reflectance of 0.25%, showing great prospect in stray light shielding. Abstract : A fluorobenzene and water assisted method is developed for rapid growth of vertical graphene (VG) arrays with a height of 144 µm at a rate of 15.9 µm h −1 . As a super black material, the VG arrays exhibit an ultralow reflectance of < 0.25% in the visible light region, showing great potential in stray light masks, energy collection and bolometer.